Targeted Program Management of the Fruit and Berry Sub-Complex of Krasnodar Region - Klochko, Elena N.; Shishkin, Viktor O.; Shichiyakh, Rustem A.; Sychanina, Svetlana N.; Smolentsev, Vitaly M. (International Review of Management and Marketing, 2016)
This article describes the state support tools and mechanisms for a fruit and berry sub-complex of Krasnodar region based on program and target technologies. The author offer the assessment Indicators of support measures` package realization efficiency for a fruit and berry sub-complex of Krasnodar Region. The results of the analysis of efficiency of realization of these measures are also presented, and the economic-mathematical model of measures` influence assessment of the state support on efficiency of a fruit and berry sub-complex development is constructed, as well as calculation of the operating influences with use of regression analysis methods. The main directions for program tools improvement aim the management of the said sub-complex of Krasnodar Region. The means for this improvement are as follows: the means of the purposes and resources validation, restructuring measures of the state support, innovative and investment development, regarding investment of public funds in introduction of innovative development allocated for productivity increase and for decrease in capital intensity. Keywords: globalization, targeted program management, state support, indicator JEL Classifications: G30; Q02; Q18